2014
DOI: 10.1177/1708538114546713
|View full text |Cite
|
Sign up to set email alerts
|

A single center experience with retrievable IVC filters

Abstract: Our study showed that a variety of IVC filters can be retrieved successfully with minimal complication rates. In more than half of our patients, IVC filters were used as permanent. Failure of retrieval was most frequently due to filter tilting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 23 publications
0
4
1
Order By: Relevance
“…This study is the first report from Asia to investigate the indications of IVC filter insertion, filter retrieval rate, and predictors of filter retrieval. We found that attempts at filter retrieval were made in 44.9% of the cases, a rate that is slightly higher than those previously reported elsewhere, 7,1416 but that remains lower than desirable. Many of the patients with retained filters seemed to be eligible for filter retrieval, as they were receiving anticoagulant therapy.…”
Section: Discussioncontrasting
confidence: 65%
“…This study is the first report from Asia to investigate the indications of IVC filter insertion, filter retrieval rate, and predictors of filter retrieval. We found that attempts at filter retrieval were made in 44.9% of the cases, a rate that is slightly higher than those previously reported elsewhere, 7,1416 but that remains lower than desirable. Many of the patients with retained filters seemed to be eligible for filter retrieval, as they were receiving anticoagulant therapy.…”
Section: Discussioncontrasting
confidence: 65%
“…In fact, many studies have found that the factor most associated with failed IVCF retrieval using standard techniques is filter tilt. [6][7][8] Although advanced retrieval techniques have higher success rates of up to 95%, severe tilt is also a leading factor associated with major complications during advanced techniques, including IVC dissection, IVC thrombus/stenosis, filter fracture with embedded strut, IVC injury with hemorrhage, and vascular injury from complicated venous access. Severe filter tilt can be managed with retrieval and replacement, but the process of having to retrieve and replace the existing filter is itself associated with procedural risks and longer radiation exposure.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5] At more than 15 degrees, filter tilting may lead to reduced efficacy of the filter in preventing pulmonary embolism (PE) and reduced success rate of retrieving the filter once it is no longer indicated. 2,3,6 Severe tilting leads to compromise of the conical design, and the larger resulting openings for passage of clot increases the risk of significant PE. Deviation of the filter hook away from the IVC midline can also cause difficulties in removing the filter using standard techniques, especially if the hook is against the caval wall.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to their complication rates, little evidence exists to show that temporary IVC filters are being retrieved routinely. Although a single-center review of the filter retrieval reported a 90.6% success rate, 14 this retrieval rate is not achieved uniformly. Most estimates of temporary IVC filter retrieval hover around 20%, whereas a systematic review found an average retrieval rate of 34%, 15 leaving these patients at risk for late complications, and worse, most of these patients likely become lost to follow-up.…”
Section: The Prevention Du Risque D'embolie Pulmonaire Parmentioning
confidence: 95%